1996
DOI: 10.2527/1996.7481915x
|View full text |Cite
|
Sign up to set email alerts
|

A cellular and endocrine characterization of the original and induced corpus luteum after administration of a gonadotropin-releasing hormone agonist or human chorionic gonadotropin on day five of the estrous cycle.

Abstract: To determine whether injection of hCG or GnRH-agonist on d 5 after estrus (d 0) has a differential functional effect on an induced and the original corpus luteum (CL), two experiments were conducted. In Exp. 1, nonlactating Holstein cows were injected on d 5 with saline (n = 4; T1), a GnRH-agonist (Buserelin, 8 micrograms i.m.; n = 4; T2), or hCG (1,000 i.u., i.v., and 2,000 i.u., i.m.; n = 4; T3). Induced CL were removed on d 13 and weights were different (GnRH-agonist < hCG). In vitro production of progester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
75
2
17

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 34 publications
12
75
2
17
Order By: Relevance
“…Previous studies in goats had associated the use of hCG to induction acessory corpus luteum, induction of estrus (Fonseca et al, 2006), and also to overcome the negative effect of premature regression of corpora lutea after superovulatory treatment (Saharrea et al, 1998). In goats, the plasma hCG profile following 500 IU hCG administration was characterized by rapid absorption (11.6h) and slow elimination (70.0h) (Saleh et al, 2012), different from cows, that lasted a total of 30h (Schmitt et al, 1996). In the present study no differences were observed in any reproductive end point evaluated in dairy goats when receiving or not hCG.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in goats had associated the use of hCG to induction acessory corpus luteum, induction of estrus (Fonseca et al, 2006), and also to overcome the negative effect of premature regression of corpora lutea after superovulatory treatment (Saharrea et al, 1998). In goats, the plasma hCG profile following 500 IU hCG administration was characterized by rapid absorption (11.6h) and slow elimination (70.0h) (Saleh et al, 2012), different from cows, that lasted a total of 30h (Schmitt et al, 1996). In the present study no differences were observed in any reproductive end point evaluated in dairy goats when receiving or not hCG.…”
Section: Discussionmentioning
confidence: 99%
“…However, circulating P4 remained lower, even after hCG treatment, in lactating cows compared with normally ovulating heifers. Eight studies that evaluated the effect of hCG on P4 concentrations from days 4 to 7 after AI in lactating dairy cows reported significant increases in circulating P4 concentrations after treatments with different doses of hCG: 3300 IU (Schmitt et al, 1996;Santos et al, 2001), 2500 IU (Stevenson et al, 2007b;Vasconcelos et al, 2011); 1500 IU (Walton et al, 1990;Hanlon et al, 2005; Kendall et al, 2009) or 1000 IU (Rajamahendran and Sianangama, 1992). Thus, treatment with hCG on day 5 after AI produces a consistent, fairly rapid (3 days delay) increase in circulating P4 in lactating dairy cows.…”
Section: Importance Of High P4 After Aimentioning
confidence: 99%
“…The use of GnRH (Lewis et al, 1990;Schmitt et al, 1996a) or hCG (Mancio et al, 1999;Santos et al, 2001) after AI increases P4 secretion due to the luteotropic effect (Kerbler et al, 1997;Santos et al, 2001) and/or induction of an accessory corpus luteum (aCL) (Schmitt et al, 1996a;Fonseca et al, 2001;Santos et al, 2001); thus, increasing progesterone concentration and, potentially, also conception.…”
Section: Introductionmentioning
confidence: 99%